High gain three‐state switching hybrid boost converter for DC microgrid applications. Issue 14 (23rd October 2019) - Maroti, Pandav Kiran; Padmanaban, Sanjeevikumar; Bhaskar, Mahajan Sagar; Meraj, Mohammad; Iqbal, Atif; Al‐Ammari, Rashid
Abstract : A novel high gain three‐state switching hybrid boost (TSS‐HB) converter for DC microgrid applications is proposed in this study. The TSS‐HB converter is developed from a conventional boost converter with voltage lift technique. The high voltage gain is achieved by the inclusion of an additional semiconductor switch. Further, this structure reduces the voltage and current stress of the switches and diodes. The proposed TSS‐HB converter operates in three switching states with the help of two different duty ratios ( k 1 and k 2 ). The power circuitry, continuous conduction mode (CCM) and discontinues conduction mode (DCM), and characteristics waveform are discussed in detail based on the theoretical background. The voltage gain and efficiency analysis of TSS‐HB in CCM is presented with consideration of non‐ideal circuit components. While boundary condition and voltage gain in DCM is discussed with ideal components. The comparison sections highlight the advantages of TSS‐HB over existed topologies with the same number of components. Further, the selection of semiconductor devices and the design of components are discussed in detail. Finally, the hardware results are presented which validate the predicted characteristics of TSS‐HB converter.